2020
DOI: 10.1136/archdischild-2019-318352
|View full text |Cite
|
Sign up to set email alerts
|

Randomised pilot trial of cash incentives for reducing paediatric asthmatic tobacco smoke exposures from maternal caregivers and members of their social network

Abstract: BackgroundThe primary aim was to evaluate the efficacy of financial incentives for reducing paediatric tobacco smoke exposures (TSEs) through motivating cigarette usage reduction among low-income maternal caregivers and members of their social network.DesignRandomised control pilot trial over a 6-month study follow-up time period. The study was undertaken from May 2017 to -May 2018. Once monthly follow-up visits occurred over the 6-month study period.SettingBaltimore City, Maryland, USA.ParticipantsWe grouped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(32 citation statements)
references
References 77 publications
(70 reference statements)
0
32
0
Order By: Relevance
“…As detailed in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses flowchart25 (see figure 1), searches identified 4268 articles; 8 met the eligibility criteria 26–33…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As detailed in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses flowchart25 (see figure 1), searches identified 4268 articles; 8 met the eligibility criteria 26–33…”
Section: Resultsmentioning
confidence: 99%
“…These are detailed in online supplemental material 2. Studies were conducted in the USA (n=7)26–30 32 33 and the UK (n=1) 31. There were five RCTs26–30 and three non-randomised studies 31–33.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations